2020
DOI: 10.3390/cancers12092473
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role for Cold Shock Protein YB-1 in Cytokinesis

Abstract: High levels of the cold shock protein Y-box-binding protein-1, YB-1, are tightly correlated with increased cell proliferation and progression. However, the precise mechanism by which YB-1 regulates proliferation is unknown. Here, we found that YB-1 depletion in several cancer cell lines and in immortalized fibroblasts resulted in cytokinesis failure and consequent multinucleation. Rescue experiments indicated that YB-1 was required for completion of cytokinesis. Using confocal imaging we found that YB-1 was es… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 85 publications
1
8
0
Order By: Relevance
“…Further experiments with constitutive active and inactive YB-1 mutants, S102D and S102A, proved our aforementioned hypothesis. However, besides S102, additional phosphorylation sites on YB-1 have been identified recently, including S165, S167, S174, S176, and S314, and the precise biological functions of these phosphorylation sites remain elusive (23,24). We and others have shown that the different types of PTM can mutually interact with each other and coordinate the intricate pathophysiological functions (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Further experiments with constitutive active and inactive YB-1 mutants, S102D and S102A, proved our aforementioned hypothesis. However, besides S102, additional phosphorylation sites on YB-1 have been identified recently, including S165, S167, S174, S176, and S314, and the precise biological functions of these phosphorylation sites remain elusive (23,24). We and others have shown that the different types of PTM can mutually interact with each other and coordinate the intricate pathophysiological functions (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the inward membrane budding (away from the cytoplasmic face) that leads to the assembly of new DENV virions evokes a range of cellular processes, such as the loading of cargo into exosomes and cytokinesis, which are mediated by the endosomal sorting complex required for transport (ESCRT) ( 55 ). Intriguingly, a role for YBX1 during these processes has been reported ( 22 25 , 56 ). Particularly, accumulating evidence supports the requirement of YBX1 for the sorting of RNA cargo, mainly small noncoding RNAs, into exosomes ( 22 25 ).…”
Section: Discussionmentioning
confidence: 98%
“…This study uses the human colorectal carcinoma cell line HCT116 originally obtained from the American Tissue Culture Collection (ATCC, Manassas, VA, USA) and recently verified by DNA Diagnostics as having an 89% match to the reference ( Supplementary Figure 12.6 ), as well as testing negative for Mycoplasma by metabolite and PCR based assays. Initially we utilised an HCT116-fluorescent, ubiquitination-based cell cycle indicator (FUCCI) cell line that was created elsewhere ( 23 , 24 ). However, this feature was not used for the cell cycling experiments and had no impact on the fluorescent detection of apoptosis, proliferation or cell viability staining during FACS collection using a Beckman Coulter Gallios cytometer, as the mCherry and mVenus fluorophores were unable to be detected by the lasers ( Supplementary Figure 12.9 ).…”
Section: Methodsmentioning
confidence: 99%